A Flexible Transient Biomemristor Based on Hybrid Structure HfO2/BSA:Au Double Layers. Issue 10 (23rd August 2020) - Li, Xiangnan; Zhang, Lei; Guo, Rui; Chen, Jingsheng; Yan, Xiaobing
Abstract: Biomemristors have attracted increasing attention in neuromorphic computing as artificial biosynapses for wearable and implantable electronic systems. So far, biomemristors have achieved a series of neural outstanding functions, such as long‐term enhancement and long‐term inhibition, spiking‐time‐dependent plasticity, and paired impulse promotion, which has further developed memristors in the field of neurobionics. However, there is a problem in conventional memristors regarding the growth position and nucleation dynamics of the conductive filaments since they cause unstable switching parameters. In this study, a new hybrid structure with HfO2 /BSA:Au (bovine serum doped with nanogold) is designed to improve biomemristor performance. The Ag/HfO2 /BSA:Au/Pt stacked devices show a reversible and excellent bipolar resistive switching behavior. Moreover, the device can faithfully emulate the apoptotic process of biological synapses. Also, the same structure is constructed on a polydimethylsiloxane flexible substrate to examine the biosynapse's functional performance under bending conditions. Finally, the memristor cell can be completely dissolved in deionized water. The hybrid biomemristor can open up a new route to improve the reliability of the biomemristor based on the overall device performance of the BSA:Au, which could significantly accelerate hybrid biomemristor practical applications in wearable, degradable, or implantable electronic systems. Abstract : The biomemristors exhibit great flexibility and outstanding artificial simulation properties. The Ag/HfO2 /BSA:Au/Pt/polydimethylsiloxane (PDMS) stacked devices show excellent retention, fast switching speed than devices without HfO2, and the biomemristors based on a PDMS flexible substrate have strong development potential in biocompatibility and development of implantable electronic devices. In addition, the device can also degrade in deionized water within 90 min.